Letterhead and logo design 8 - Top Design Studio (Los Angeles, Calif.) (Gloucester, Mass. : Rockport, 2003)
Presents more than five hundred letterhead and logo examples from top design firms
Professional Services 16 -- Creative Services 80 -- Retail, Restaurant, and Hospitality 118 -- Education, Health, and Nonprofit 154 -- Recreation and Entertainment 174
Includes index
Keywords: Letterheads -- Design; Logos (Symbols) -- Design; Graphic arts